Enhancing SO3 hydrolysis and nucleation: the role of formic sulfuric anhydride - R. Wang; R. Li; S. Chen; R. Mu; C. Zhang; X. Ma; M. Khan; T. Zhang (Atmospheric Chemistry and Physics)
Although the nucleation route driven by sulfuric acid (H2SO4) and ammonia (NH3) primarily dominates new particle formation (NPF) in the atmosphere, exploring the role of other trace species in the H2SO4–NH3 system is crucial for a more comprehensive insight into NPF processes. Formic sulfuric anhydride (FSA) has been observed in the atmospheric environment and is found in abundance in atmospheric fine particles. Nevertheless, its effect on SO3 hydrolysis and NPF remains poorly understood. Here, we studied the enhancing effect of FSA on gaseous and interfacial SO3 hydrolysis as well as its impact on H2SO4–NH3-driven NPF occurring through quantum chemical calculations, Atmospheric Cluster Dynamics Code (ACDC) kinetics combined with Born–Oppenheimer molecular dynamics (BOMD). Gaseous-phase findings indicate that FSA-catalyzed SO3 hydrolysis is nearly barrierless. At an [FSA] = 107 molecules cm−3, this reaction competes effectively with SO3 hydrolysis in the presence of HNO3 (109 molecules cm−3), HCOOH (108 molecules cm−3) and H2SO4 (106 molecules cm−3) in the range of 280.0–320.0 K. At the gas–liquid nanodroplet interface, BOMD simulations reveal that FSA-mediated SO3 hydrolysis follows a stepwise mechanism, completing within a few picoseconds. Notably, FSA enhances the formation rate of H2SO4–NH3 clusters by over 105 times in regions with relatively high [FSA] at elevated temperatures. Additionally, the interfacial FSA− ion has the ability to appeal precursor species for particle formation from the gaseous phase to the water nanodroplet interface, thereby facilitating particle growth. These results present new insights into both the pathways of H2SO4 formation and aerosol particle growth in the polluted boundary layer.